FAKTOR EKSTERNAL DAN INTERNAL YANG MEMPENGARUHI PRESIDEN DONALD TRUMP UNTUK MENGAKUI STATUS KOTA YERUSALEM SEBAGAI IBUKOTA ISRAEL - Alama, Agra Haydar; Utomo, Tri Cahyo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
On December 6th 2017, the United States under Donald Trump presidency recognized the political status of Jerusalem City as the capital of Israel. Right away the decision gathered criticisms and controversy. States all over the world especially Muslim majority countries gathered on the streets to protest the policy. It was to be expected as Jerusalem is considered to be one of the key elements for peace process between Israelis and the Palestinians. Although the United States and Israel have a very close relations, there had been no president of the United States before President Trump to issue such declaration in their presidencies. This research aims to look for what factors that influenced President Trump’s decision regarding Jerusalem. In order to do that, this research uses neoclassical realism as a framework to analyze the case. Broadly speaking, this theory analyzes foreign policies from external and internal factors. Accordingly, this research argues that international circumstances were very supporting for the United States to issue the foreign policy. Moreover, President Trump’s closest advisers and his supporter bases were those who had pro-Israel view so that it’s not surprising that if President Trump wanted to fulfill their wishes in order to maintain and increase the president’s popularity among the people of the United States.